Seeing smells: development of an optoelectronic nose - Kenneth S. Suslick (Química Nova, 2007)
The development of an array of chemically-responsive dyes on a porous membrane and in its use as a general sensor for odors and volatile organic compounds (VOCs) is reviewed. These colorimetric sensor arrays (CSA) act as an "optoelectronic nose" by using an array of multiple dyes whose color changes are based on the full range of intermolecular interactions. The CSA is digitally imaged before and after exposure and the resulting difference map provides a digital fingerprint for any VOC or mixture of odorants. The result is an enormous increase in discriminatory power among odorants compared to prior electronic nose technologies. For the detection of biologically important analytes, including amines, carboxylic acids, and thiols, high sensitivities (ppbv) have been demonstrated. The array is essentially non-responsive to changes in humidity due to the hydrophobicity of the dyes and membrane.